Enhancing Cultural and Religious Tourism Students' Competence through PjBL: Collaborative Learning in MICE (Meeting, Incentive, Convention, and Exhibition) - Nadeak, Tio R J; Saragih, Herlina; Silalahi, Mery; Smj, Williem Kennedy (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to analyze the effectiveness of Project-Based Learning (PjBL) in developing 21st-century skills among students of the Cultural and Religious Tourism Study Program at the Tarutung State Christian Institute through the MICE (Meeting, Incentive, Convention, and Exhibition) course. Employing a qualitative case study approach, the research involved 37 sixth-semester students and utilized questionnaires, interviews, and documentation to collect data. The findings show that the implementation of PjBL significantly improves students’ critical thinking, creative thinking, communication, and collaboration skills. Real-life project experiences through MICE activities encouraged students to analyze problems, generate innovative ideas, work collaboratively in teams, and communicate effectively with various stakeholders. Students also reported increased motivation, independence, and engagement throughout the learning process. These results underscore the practical relevance of PjBL in preparing students for the dynamic demands of the tourism industry. Future research is recommended to expand the application of PjBL in other tourism-related subjects and to explore its impact on students’ digital and leadership competencies.